High flame-retardant and aging-resistant copper core cable and preparation process thereof

CN122991750APending Publication Date: 2026-10-27GUANGDONG LONG RANG CABLE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611252420.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0016]与现有技术相比,本发明的高阻燃耐老化铜芯电缆及其制备工艺,通过设置绝缘层与阻燃护套层之间特有的EVA过渡粘结层,有效消除了层间因热膨胀系数差异导致的界面应力集中,确保高温工况下各功能层结构的稳固结合;同时,利用绝缘层的膨胀型阻燃体系与阻燃护套层的陶瓷化阻燃体系在火灾高温下发生协同烧蚀,形成互嵌互补的“膨胀炭层-陶瓷骨架”复合阻燃屏障,避免了单一防护屏障的坍塌与裂缝蔓延,从而在显著提升电缆整体阻燃等级与成束燃烧通过率的同时,有效保障了其在苛刻热环境下的结构完整性与长期服役寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991750A_ABST
    Figure CN122991750A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high flame-retardant ageing-resistant copper core cable and preparation process thereof, belong to wire and cable manufacturing technical field, from inside to outside include successively: conductor layer, inner shielding layer, insulating layer, flame-retardant sheath layer and outer sheath;The insulating layer is formed by intumescent flame-retardant crosslinked ethylene-vinyl acetate copolymer composition, the flame-retardant sheath layer is formed by ceramic flame-retardant crosslinked ternary ethylene-propylene rubber composition;Ethylene-vinyl acetate transition adhesive layer is provided between the insulating layer and the flame-retardant sheath layer, the conductor layer is multiple stranded copper core, the copper core surface is covered with nano silver-graphene composite plating layer, the thickness of the plating layer is 5nm-20nm;Avoid the collapse and crack spread of single protective barrier, so as to significantly improve the overall flame-retardant grade of cable and bundle burning pass rate, while effectively guaranteeing its structural integrity and long-term service life in harsh thermal environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wire and cable manufacturing technology, specifically relating to a high flame-retardant and aging-resistant copper core cable and its preparation process. Background Technology

[0002] Copper core cables are widely used in the power transmission field, and their flame-retardant performance and long-term operational reliability are key indicators for measuring product quality. Conventional copper core cables in existing technology typically use only a single layer of flame-retardant sheath, or add a single flame retardant to the insulation layer to achieve basic flame-retardant protection.

[0003] However, existing technologies have the following drawbacks: First, single-layer or single-flame-retardant systems struggle to form a continuous and dense protective barrier under high-temperature fire conditions. Furthermore, due to differences in the thermal expansion coefficients and thermal decomposition behaviors of different functional layers, they often react independently during high-temperature ablation, failing to achieve a synergistic and complementary flame-retardant effect. Second, existing cables often employ simple physical bonding or direct co-extrusion between the insulation layer and the flame-retardant sheath, lacking a dedicated functional interlayer transition structure. During long-term operation and aging, this structure suffers from insufficient interlayer bonding, easily leading to interface peeling, delamination, or cracking. This, in turn, accelerates the intrusion of heat and oxygen, severely weakening the overall flame-retardant performance and service life of the cable. Third, existing layered cable structures struggle to ensure stable bonding between layers while simultaneously ensuring the synergistic effect of the flame-retardant system at high temperatures.

[0004] Therefore, in order to address the above-mentioned technical problems, it is necessary to provide a high flame-retardant and aging-resistant copper core cable and its manufacturing process. Summary of the Invention

[0005] The purpose of this invention is to provide a high flame-retardant and aging-resistant copper core cable and its manufacturing process, aiming to overcome the problems of single flame-retardant system, poor interlayer interface bonding, and insufficient synergistic protection at high temperatures in existing technologies.

[0006] To achieve the above objectives, a specific embodiment of the present invention provides the following technical solution: A high flame-retardant and aging-resistant copper core cable comprises, from the inside out: a conductor layer, an inner shielding layer, an insulation layer, a flame-retardant sheath layer, and an outer sheath; The insulating layer is formed of an intumescent flame-retardant cross-linked ethylene-vinyl acetate copolymer composition, and the flame-retardant sheath layer is formed of a ceramicized flame-retardant cross-linked ethylene propylene diene monomer rubber composition. An ethylene-vinyl acetate transition bonding layer is provided between the insulation layer and the flame-retardant sheath layer.

[0007] In one or more embodiments of the present invention, the conductor layer is a multi-stranded copper core, and the surface of the copper core is covered with a nano-silver-graphene composite coating, the thickness of which is 5nm-20nm.

[0008] In one or more embodiments of the present invention, the intumescent flame-retardant crosslinked ethylene-vinyl acetate copolymer composition of the insulating layer comprises the following components in parts by weight: 100 parts of ethylene-vinyl acetate copolymer, 15-25 parts of ammonium polyphosphate, 8-12 parts of melamine cyanuric acid, 6-10 parts of pentaerythritol, 2-5 parts of dicumyl peroxide, 3-8 parts of nano silica, 0.5-1.5 parts of antioxidant 1010, and 0.5-1.0 parts of antioxidant 168.

[0009] In one or more embodiments of the present invention, the ceramicized flame-retardant crosslinked EPDM rubber composition of the flame-retardant sheath layer comprises the following components in parts by weight: 100 parts of EPDM rubber, 10-15 parts of expandable graphite, 20-35 parts of glass powder, 5-10 parts of zinc borate, 40-60 parts of magnesium hydroxide surface modified with silane coupling agent, 2-4 parts of di-tert-butyl peroxide, and 0.5-1.0 parts of antioxidant 445.

[0010] In one or more embodiments of the present invention, the thickness of the ethylene-vinyl acetate transition adhesive layer is 0.1mm-0.3mm, and the interlayer peel strength of the insulating layer and the flame-retardant sheath layer after being bonded by the transition adhesive layer is ≥0.5N / mm.

[0011] In one or more embodiments of the present invention, the oxygen index of the cable is ≥32% and passes the VW-1 vertical burning test; the outer sheath is a low-smoke halogen-free flame-retardant polyolefin layer with an oxygen index ≥36%.

[0012] In one or more embodiments of the present invention, the thickness ratio of the insulation layer, the flame-retardant sheath layer, and the outer sheath is (1.0-1.5):(0.8-1.2):(0.5-0.8), and the overall outer diameter of the cable is 10mm-80mm.

[0013] In one or more embodiments of the present invention, after the cable undergoes a thermal aging test at 120°C for 168 hours, the elongation at break retains ≥80%; the expanded carbon layer formed by the insulation layer at high temperature and the ceramic skeleton formed by the flame-retardant sheath layer at high temperature undergo synergistic ablation to form a composite flame-retardant barrier of "expanded carbon layer-ceramic skeleton".

[0014] A manufacturing process for a high flame-retardant and aging-resistant copper core cable as described above includes the following steps: Step 1: The inner shielding layer and the insulating layer are simultaneously extruded onto the outer surface of the conductor layer through a three-layer co-extrusion process. The extrusion temperatures from the barrel to the die head are 100℃, 110℃, 120℃, 130℃, and 125℃ respectively. Step 2: Coat the outer surface of the insulation layer with an ethylene-vinyl acetate transition adhesive layer; Step 3: Extrude a flame-retardant sheath layer onto the outer surface of the transition adhesive layer, and then extrude an outer sheath onto the outer surface of the flame-retardant sheath layer.

[0015] In one or more embodiments of the present invention, in step one, the insulating layer is immediately subjected to electron beam irradiation crosslinking after extrusion, with an irradiation dose of 8Mrad-12Mrad and a crosslinking degree of ≥75%; in step three, the flame-retardant sheath layer is subjected to warm water crosslinking treatment after extrusion, with a crosslinking temperature of 80℃-90℃, a crosslinking time of 12 hours-24 hours, and a crosslinking degree of ≥70%.

[0016] Compared with existing technologies, the high flame-retardant and aging-resistant copper core cable and its manufacturing process of the present invention effectively eliminate the interface stress concentration caused by the difference in thermal expansion coefficients between the insulation layer and the flame-retardant sheath layer by setting a unique EVA transition bonding layer, ensuring the stable bonding of each functional layer structure under high temperature conditions. At the same time, the expansion-type flame-retardant system of the insulation layer and the ceramic flame-retardant system of the flame-retardant sheath layer undergo synergistic ablation under high temperature fire conditions to form an interlocking and complementary "expanded carbon layer-ceramic skeleton" composite flame-retardant barrier, avoiding the collapse and crack propagation of a single protective barrier. Thus, while significantly improving the overall flame-retardant rating and bundled combustion pass rate of the cable, it effectively ensures its structural integrity and long service life under harsh thermal environments. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a schematic diagram of the cross-sectional structure of the high flame-retardant and aging-resistant copper core cable of the present invention; Figure 2 This is a schematic diagram of the synergistic flame-retardant mechanism of the expanded carbon layer-ceramic skeleton under high-temperature ablation according to the present invention; Figure 3 This is a flowchart of the cable manufacturing process of the present invention.

[0019] Explanation of key figure labels: 1. Conductor layer; 2. Inner shielding layer; 3. Insulating layer; 4. Flame-retardant sheath layer; 5. Outer sheath. Detailed Implementation

[0020] To enable those skilled in the art to better understand the technical solutions in this disclosure, the technical solutions in the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments in this disclosure, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this disclosure.

[0021] like Figures 1 to 3 As shown, this embodiment is a high flame-retardant and aging-resistant copper core cable; electrolytic copper with a purity of ≥99.9% is selected, and multi-strand stranded copper core is made by drawing and stranding, with a single wire diameter of 0.20mm-0.50mm and a stranding pitch ratio of 8-12 times; the copper core is placed in an inert atmosphere furnace and annealed at 400℃-500℃ for 1-3 hours.

[0022] Subsequently, the annealed copper core was placed in an electrochemical deposition tank, and a nano-silver-graphene composite coating was deposited on the surface of the copper core using an electrochemical deposition method. The concentration of silver ions in the plating solution was 10 g / L-20 g / L, the concentration of graphene dispersion was 0.5 g / L-2 g / L, and the deposition current density was 0.5 A / dm³. 2 -1.5A / dm 2 The coating time is controlled to be 10-30 minutes to obtain a nano-silver-graphene composite coating with a thickness of 5nm-20nm.

[0023] The inner shielding layer 2 is made of semi-conductive cross-linked polyethylene material. This material, by weight, comprises: 100 parts cross-linked polyethylene resin, 40-60 parts conductive carbon black, 0.2-0.5 parts antioxidant 300, and 1-2 parts dicumyl peroxide (DCP). After uniform mixing in a high-speed mixer, the mixture is granulated in a twin-screw extruder at 110-130°C for later use. The thickness of the inner shielding layer 2 is 10%-15% of the thickness of the insulation layer 3, typically 0.8 mm-1.0 mm.

[0024] Insulation layer 3 is formed from an intumescent flame-retardant crosslinked ethylene-vinyl acetate copolymer (EVA) composition. The components are weighed according to the following parts by weight: 100 parts of ethylene-vinyl acetate copolymer (VA content 28%-33%), 20 parts of ammonium polyphosphate (APP), 10 parts of melamine cyanuric acid (MCA), 8 parts of pentaerythritol (PER), 5 parts of nano silica, 3.5 parts of dicumyl peroxide (DCP), 1.0 part of antioxidant 1010, 0.8 parts of antioxidant 168, and 0.8 parts of zinc stearate.

[0025] Add all the above components to a high-speed mixer and mix for 10-15 minutes at room temperature at a speed of 600-800 rpm. Add the mixture to a twin-screw extruder for granulation. The extrusion temperatures are: Zone 1 105℃, Zone 2 115℃, Zone 3 125℃, and Die Head 120℃, with a screw speed of 200-300 rpm. After granulation, cool at room temperature to obtain 3-granule insulating layer material.

[0026] The flame-retardant sheath layer 4 is formed from a ceramicized flame-retardant crosslinked ethylene propylene diene monomer (EPDM) rubber composition. The components are weighed according to the following parts by weight: 100 parts EPDM rubber, 12 parts expandable graphite, 28 parts glass powder, 5 parts zinc borate, 50 parts magnesium hydroxide surface-treated with γ-aminopropyltriethoxysilane, 3 parts bis-tert-butyl peroxide (BIPB), and 4450.8 parts antioxidant.

[0027] Add EPDM rubber to a Banbury mixer and mix at 100℃-110℃ for 3-5 minutes. Add expandable graphite, glass powder, zinc borate, and modified magnesium hydroxide, and continue mixing for 5-8 minutes. Finally, add crosslinking agent BIPB and antioxidant 445, and mix at 105℃ for 3 minutes. Discharge the mixture. Sheet the compound on a two-roll mill and cool it for later use.

[0028] The transition binder layer is composed of an ethylene-vinyl acetate (EVA) copolymer and a compatibilizer (such as maleic anhydride-grafted EVA). The EVA resin comprises 100 parts, and the maleic anhydride-grafted EVA comprises 5-10 parts. The components are mixed uniformly in a Banbury mixer at 100℃-120℃, and then extruded and granulated using a single-screw extruder for later use. The extrusion temperatures of the transition binder layer are set at 110℃, 115℃, and 120℃, and the binder layer granules are obtained after cooling.

[0029] The outer sheath 5 is made of low-smoke, halogen-free, flame-retardant polyolefin material. By weight, it comprises: 100 parts ethylene-vinyl acetate copolymer (VA content 28%), 120-150 parts aluminum hydroxide, 15-20 parts melamine cyanuric acid, 0.5 parts antioxidant 1010, and 0.5 parts antioxidant 168. The above components are granulated in a twin-screw extruder for later use.

[0030] like Figures 1 to 3 As shown, this embodiment illustrates the manufacturing process of a high flame-retardant and aging-resistant copper core cable. The inner shielding layer 2 granules and insulation layer 3 granules obtained in the previous embodiment are combined with the prepared conductor layer 1 and extruded simultaneously in a twin-screw extruder using a three-layer co-extrusion process. The extruder body temperature is set to 100℃ in zone 1, 110℃ in zone 2, 120℃ in zone 3, 130℃ in zone 4, and the die head temperature is 125℃. The screw speed is 250 rpm. After extrusion, the cable is cooled and shaped using a cooling water bath.

[0031] After the insulation layer 3 is extruded, the wire core is immediately subjected to cross-linking treatment by an electron beam irradiation device, with the irradiation dose set to 10Mrad and the cross-linking degree controlled to be ≥75%.

[0032] Using a co-extrusion die, the transition adhesive layer granules obtained in the above embodiment are coated with a 0.2 mm thick EVA transition adhesive layer on the outer surface of the insulating layer 3 at a coating temperature of 120℃-130℃.

[0033] Using a single-screw extruder, the flame-retardant sheath layer 4 compound obtained in the above embodiment is extruded onto the outer surface of the transition bonding layer at an extrusion temperature of 110℃-125℃; subsequently, using another single-screw extruder, the outer sheath 5 obtained in the above embodiment is extruded onto the outer surface of the flame-retardant sheath layer 4 at an extrusion temperature of 130℃-150℃, so that the outer sheath 5 and the flame-retardant sheath layer 4 are directly bonded together.

[0034] After extrusion of the sheath and outer sheath 5, the cable enters the warm water crosslinking tank and undergoes warm water crosslinking treatment in a water bath at 85℃ for 18 hours, with a crosslinking degree ≥70%.

[0035] After cross-linking, the cable is cooled, pulled, and wound to obtain the finished cable. The measured thickness ratio of the insulation layer 3, the flame-retardant sheath layer 4, and the outer sheath 5 is 1.2:1.0:0.6, and the overall cable outer diameter is 20mm.

[0036] The cables prepared in the above embodiments were subjected to performance tests, and the test results are as follows: Oxygen index test: The oxygen index of the cable is 33.5% according to GB / T 2406 standard.

[0037] Vertical burning test: The VW-1 vertical burning test was conducted according to UL 1581 standard. The sample self-extinguished within 60 seconds after the flame was applied, and no dripping material ignited the degreased cotton. The sample successfully passed the VW-1 test.

[0038] Interlayer peel strength test: The peel strength between the insulation layer 3 and the flame-retardant sheath layer 4 was tested according to GB / T 2790 standard. The result was 0.62 N / mm, which meets the requirement of ≥0.5 N / mm.

[0039] Thermal aging performance test: After aging at 120℃ for 168 hours according to GB / T 2951.12 standard, the elongation at break retention rate of insulation layer 3 and sheath layer was tested, and the result was 82.5%.

[0040] Verification of the synergistic effect of high temperature ablation resistance: The cable was placed under a high temperature flame of 800℃ for 30 minutes. After it was removed, the cross section was observed. It can be seen that the insulation layer 3 formed a dense and continuous porous expanded carbon layer, and the flame-retardant sheath layer 4 was sintered to form a complete ceramic skeleton. Moreover, the carbon layer and the ceramic skeleton are interlocked at the interface without obvious delamination, forming a composite flame-retardant barrier of "expanded carbon layer-ceramic skeleton".

[0041] The cable structure of Comparative Example 1 is the same as that of the above embodiments, but without the ethylene-vinyl acetate transition bonding layer between the insulation layer 3 and the flame-retardant sheath layer 4. That is, the insulation layer 3 and the flame-retardant sheath layer 4 are directly bonded by physical co-extrusion.

[0042] Comparative Example 1 test results: interlayer peel strength was 0.15 N / mm; after being burned at 800℃, obvious delamination cracks appeared between the insulation layer 3 (expanded carbon layer) and the flame-retardant sheath layer 4 (ceramic skeleton), and heat penetrated into the interior through the cracks; the elongation at break after thermal aging was only 65%, indicating that the lack of a transition bonding layer caused interlayer bonding failure, leading to oxygen intrusion and significantly reducing the aging resistance.

[0043] In summary, this invention constructs a stable composite flame-retardant barrier of "expanded char layer-ceramic skeleton" through the synergistic cooperation of "insulation layer 3 intumescent flame retardant + flame retardant sheath layer 4 ceramic flame retardant" and the introduction of a special transition bonding layer between the layers. This effectively solves the problems of poor synergy of flame-retardant functional layers, easy peeling between layers, and insufficient high-temperature aging performance, and has significant technological progress and outstanding substantive features.

[0044] It will be apparent to those skilled in the art that this disclosure is not limited to the details of the exemplary embodiments described above, and that this disclosure can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of this disclosure is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within this disclosure. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0045] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A high flame-retardant and aging-resistant copper core cable, characterized in that, From the inside out, it includes: conductor layer, inner shielding layer, insulation layer, flame-retardant sheath layer, and outer sheath; The insulating layer is formed of an intumescent flame-retardant cross-linked ethylene-vinyl acetate copolymer composition, and the flame-retardant sheath layer is formed of a ceramicized flame-retardant cross-linked ethylene propylene diene monomer rubber composition. An ethylene-vinyl acetate transition bonding layer is provided between the insulation layer and the flame-retardant sheath layer.

2. The high flame-retardant and aging-resistant copper core cable according to claim 1, characterized in that, The conductor layer is a multi-stranded copper core, and the surface of the copper core is covered with a nano-silver-graphene composite coating with a thickness of 5nm-20nm.

3. The high flame-retardant and aging-resistant copper core cable according to claim 1, characterized in that, The intumescent flame-retardant crosslinked ethylene-vinyl acetate copolymer composition of the insulating layer comprises the following components in parts by weight: 100 parts of ethylene-vinyl acetate copolymer, 15-25 parts of ammonium polyphosphate, 8-12 parts of melamine cyanuric acid, 6-10 parts of pentaerythritol, 2-5 parts of dicumyl peroxide, 3-8 parts of nano silica, 0.5-1.5 parts of antioxidant 1010, and 0.5-1.0 parts of antioxidant 168.

4. The high flame-retardant and aging-resistant copper core cable according to claim 1, characterized in that, The ceramicized flame-retardant crosslinked EPDM rubber composition of the flame-retardant sheath layer comprises the following components in parts by weight: 100 parts EPDM rubber, 10-15 parts expandable graphite, 20-35 parts glass powder, 5-10 parts zinc borate, 40-60 parts magnesium hydroxide surface modified with silane coupling agent, 2-4 parts di-tert-butyl peroxide, and 0.5-1.0 parts antioxidant 445.

5. The high flame-retardant and aging-resistant copper core cable according to claim 1, characterized in that, The thickness of the ethylene-vinyl acetate transition adhesive layer is 0.1mm-0.3mm, and the interlayer peel strength of the insulating layer and the flame-retardant sheath layer after being bonded by the transition adhesive layer is ≥0.5N / mm.

6. The high flame-retardant and aging-resistant copper core cable according to claim 1, characterized in that, The cable has an oxygen index ≥32% and has passed the VW-1 vertical burning test; the outer sheath is a low-smoke halogen-free flame-retardant polyolefin layer with an oxygen index ≥36%.

7. The high flame-retardant and aging-resistant copper core cable according to claim 1, characterized in that, The thickness ratio of the insulation layer, the flame-retardant sheath layer, and the outer sheath is (1.0-1.5):(0.8-1.2):(0.5-0.8), and the overall outer diameter of the cable is 10mm-80mm.

8. The high flame-retardant and aging-resistant copper core cable according to claim 1, characterized in that, After undergoing a 120℃×168h thermal aging test, the cable retains an elongation at break of ≥80%; the expanded carbon layer formed by the insulation layer at high temperature and the ceramic skeleton formed by the flame-retardant sheath layer at high temperature undergo synergistic ablation to form a composite flame-retardant barrier of "expanded carbon layer-ceramic skeleton".

9. A manufacturing process for a high flame-retardant and aging-resistant copper core cable as described in any one of claims 1-5, characterized in that, Includes the following steps: Step 1: The inner shielding layer and the insulating layer are simultaneously extruded onto the outer surface of the conductor layer through a three-layer co-extrusion process. The extrusion temperatures from the barrel to the die head are 100℃, 110℃, 120℃, 130℃, and 125℃ respectively. Step 2: Coat the outer surface of the insulation layer with an ethylene-vinyl acetate transition adhesive layer; Step 3: Extrude a flame-retardant sheath layer onto the outer surface of the transition adhesive layer, and then extrude an outer sheath onto the outer surface of the flame-retardant sheath layer.

10. The preparation process according to claim 9, characterized in that, In step one, the insulating layer is immediately cross-linked by electron beam irradiation after extrusion, with an irradiation dose of 8-12 Mrad and a cross-linking degree of ≥75%. In step three, the flame-retardant sheath layer is cross-linked by warm water after extrusion, with a cross-linking temperature of 80-90℃, a cross-linking time of 12-24 hours, and a cross-linking degree of ≥70%.